1.11: Difference between revisions

From testwiki
Jump to navigation Jump to search
 
Line 14: Line 14:
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
! scope="col" style="position: sticky; top: 0;" | Numeric<br>Mathematica
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/1.11.E3 1.11.E3] || [[Item:Q383|<math>b_{k} = \alpha b_{k+1}+a_{k}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>b_{k} = \alpha b_{k+1}+a_{k}</syntaxhighlight> || <math>k = n-1</math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">b[k] = alpha*b[k + 1]+ a[k]</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[b, k] == \[Alpha]*Subscript[b, k + 1]+ Subscript[a, k]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/1.11.E3 1.11.E3] || <math qid="Q383">b_{k} = \alpha b_{k+1}+a_{k}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>b_{k} = \alpha b_{k+1}+a_{k}</syntaxhighlight> || <math>k = n-1</math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">b[k] = alpha*b[k + 1]+ a[k]</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[b, k] == \[Alpha]*Subscript[b, k + 1]+ Subscript[a, k]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/1.11.E5 1.11.E5] || [[Item:Q385|<math>c_{k} = \alpha c_{k+1}+b_{k}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>c_{k} = \alpha c_{k+1}+b_{k}</syntaxhighlight> || <math>k = n-1</math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">c[k] = alpha*c[k + 1]+ b[k]</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[c, k] == \[Alpha]*Subscript[c, k + 1]+ Subscript[b, k]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/1.11.E5 1.11.E5] || <math qid="Q385">c_{k} = \alpha c_{k+1}+b_{k}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>c_{k} = \alpha c_{k+1}+b_{k}</syntaxhighlight> || <math>k = n-1</math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">c[k] = alpha*c[k + 1]+ b[k]</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[c, k] == \[Alpha]*Subscript[c, k + 1]+ Subscript[b, k]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/1.11#E10Xa 1.11#E10Xa] || [[Item:Q392|<math>\displaystyle\sum_{1\leq j<k\leq n}z_{j}z_{k} = a_{n-2}/a_{n}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\displaystyle\sum_{1\leq j<k\leq n}z_{j}z_{k} = a_{n-2}/a_{n}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">sum(sum(z[j]*z[k], k = j + 1..n), j = 1..k - 1) = a[n - 2]/a[n]</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Sum[Sum[Subscript[z, j]*Subscript[z, k], {k, j + 1, n}, GenerateConditions->None], {j, 1, k - 1}, GenerateConditions->None] == Subscript[a, n - 2]/Subscript[a, n]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/1.11#E10Xa 1.11#E10Xa] || <math qid="Q392">\displaystyle\sum_{1\leq j<k\leq n}z_{j}z_{k} = a_{n-2}/a_{n}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\displaystyle\sum_{1\leq j<k\leq n}z_{j}z_{k} = a_{n-2}/a_{n}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">sum(sum(z[j]*z[k], k = j + 1..n), j = 1..k - 1) = a[n - 2]/a[n]</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Sum[Sum[Subscript[z, j]*Subscript[z, k], {k, j + 1, n}, GenerateConditions->None], {j, 1, k - 1}, GenerateConditions->None] == Subscript[a, n - 2]/Subscript[a, n]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/1.11#Ex4 1.11#Ex4] || [[Item:Q396|<math>D = b^{2}-4ac</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>D = b^{2}-4ac</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(- 4*(p)^(3)- 27*(q)^(2)) = (b)^(2)- 4*a*c</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(- 4*(p)^(3)- 27*(q)^(2)) == (b)^(2)- 4*a*c</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/1.11#Ex4 1.11#Ex4] || <math qid="Q396">D = b^{2}-4ac</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>D = b^{2}-4ac</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(- 4*(p)^(3)- 27*(q)^(2)) = (b)^(2)- 4*a*c</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(- 4*(p)^(3)- 27*(q)^(2)) == (b)^(2)- 4*a*c</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/1.11#Ex10 1.11#Ex10] || [[Item:Q403|<math>\rho = -\tfrac{1}{2}+\tfrac{1}{2}\sqrt{-3}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\rho = -\tfrac{1}{2}+\tfrac{1}{2}\sqrt{-3}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">rho = -(1)/(2)+(1)/(2)*sqrt(- 3)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">\[Rho] == -Divide[1,2]+Divide[1,2]*Sqrt[- 3]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/1.11#Ex10 1.11#Ex10] || <math qid="Q403">\rho = -\tfrac{1}{2}+\tfrac{1}{2}\sqrt{-3}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\rho = -\tfrac{1}{2}+\tfrac{1}{2}\sqrt{-3}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">rho = -(1)/(2)+(1)/(2)*sqrt(- 3)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">\[Rho] == -Divide[1,2]+Divide[1,2]*Sqrt[- 3]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/1.11#Ex11 1.11#Ex11] || [[Item:Q404|<math>\rho^{2} = e^{-2\pi i/3}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\rho^{2} = e^{-2\pi i/3}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(rho)^(2) = exp(- 2*Pi*I/3)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">\[Rho]^(2) == Exp[- 2*Pi*I/3]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/1.11#Ex11 1.11#Ex11] || <math qid="Q404">\rho^{2} = e^{-2\pi i/3}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\rho^{2} = e^{-2\pi i/3}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(rho)^(2) = exp(- 2*Pi*I/3)</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">\[Rho]^(2) == Exp[- 2*Pi*I/3]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/1.11#Ex13 1.11#Ex13] || [[Item:Q406|<math>p = (-3a^{2}+8b)/8</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>p = (-3a^{2}+8b)/8</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">p = (- 3*(a)^(2)+ 8*b)/8</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">p == (- 3*(a)^(2)+ 8*b)/8</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/1.11#Ex13 1.11#Ex13] || <math qid="Q406">p = (-3a^{2}+8b)/8</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>p = (-3a^{2}+8b)/8</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">p = (- 3*(a)^(2)+ 8*b)/8</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">p == (- 3*(a)^(2)+ 8*b)/8</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/1.11#Ex14 1.11#Ex14] || [[Item:Q407|<math>q = (a^{3}-4ab+8c)/8</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>q = (a^{3}-4ab+8c)/8</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">q = ((a)^(3)- 4*a*b + 8*c)/8</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">q == ((a)^(3)- 4*a*b + 8*c)/8</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/1.11#Ex14 1.11#Ex14] || <math qid="Q407">q = (a^{3}-4ab+8c)/8</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>q = (a^{3}-4ab+8c)/8</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">q = ((a)^(3)- 4*a*b + 8*c)/8</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">q == ((a)^(3)- 4*a*b + 8*c)/8</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/1.11#Ex15 1.11#Ex15] || [[Item:Q408|<math>r = (-3a^{4}+16a^{2}b-64ac+256d)/256</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>r = (-3a^{4}+16a^{2}b-64ac+256d)/256</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">r = (- 3*(a)^(4)+ 16*(a)^(2)* b - 64*a*c + 256*d)/256</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">r == (- 3*(a)^(4)+ 16*(a)^(2)* b - 64*a*c + 256*d)/256</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/1.11#Ex15 1.11#Ex15] || <math qid="Q408">r = (-3a^{4}+16a^{2}b-64ac+256d)/256</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>r = (-3a^{4}+16a^{2}b-64ac+256d)/256</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">r = (- 3*(a)^(4)+ 16*(a)^(2)* b - 64*a*c + 256*d)/256</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">r == (- 3*(a)^(4)+ 16*(a)^(2)* b - 64*a*c + 256*d)/256</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/1.11.E18 1.11.E18] || [[Item:Q410|<math>z^{3}-2pz^{2}+(p^{2}-4r)z+q^{2} = 0</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>z^{3}-2pz^{2}+(p^{2}-4r)z+q^{2} = 0</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(z)^(3)- 2*p*(z)^(2)+((p)^(2)- 4*r)*z + (q)^(2) = 0</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(z)^(3)- 2*p*(z)^(2)+((p)^(2)- 4*r)*z + (q)^(2) == 0</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/1.11.E18 1.11.E18] || <math qid="Q410">z^{3}-2pz^{2}+(p^{2}-4r)z+q^{2} = 0</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>z^{3}-2pz^{2}+(p^{2}-4r)z+q^{2} = 0</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(z)^(3)- 2*p*(z)^(2)+((p)^(2)- 4*r)*z + (q)^(2) = 0</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(z)^(3)- 2*p*(z)^(2)+((p)^(2)- 4*r)*z + (q)^(2) == 0</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/1.11.E20 1.11.E20] || [[Item:Q415|<math>\sqrt{-\theta_{1}}\;\sqrt{-\theta_{2}}\;\sqrt{-\theta_{3}} = -q</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\sqrt{-\theta_{1}}\;\sqrt{-\theta_{2}}\;\sqrt{-\theta_{3}} = -q</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">sqrt(- theta[1])*sqrt(- theta[2])*sqrt(- theta[3]) = - q</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Sqrt[- Subscript[\[Theta], 1]]*Sqrt[- Subscript[\[Theta], 2]]*Sqrt[- Subscript[\[Theta], 3]] == - q</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/1.11.E20 1.11.E20] || <math qid="Q415">\sqrt{-\theta_{1}}\;\sqrt{-\theta_{2}}\;\sqrt{-\theta_{3}} = -q</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>\sqrt{-\theta_{1}}\;\sqrt{-\theta_{2}}\;\sqrt{-\theta_{3}} = -q</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">sqrt(- theta[1])*sqrt(- theta[2])*sqrt(- theta[3]) = - q</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Sqrt[- Subscript[\[Theta], 1]]*Sqrt[- Subscript[\[Theta], 2]]*Sqrt[- Subscript[\[Theta], 3]] == - q</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/1.11.E22 1.11.E22] || [[Item:Q417|<math>z^{n} = a+ib</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>z^{n} = a+ib</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(z)^(n) = a + I*b</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(z)^(n) == a + I*b</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/1.11.E22 1.11.E22] || <math qid="Q417">z^{n} = a+ib</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>z^{n} = a+ib</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(z)^(n) = a + I*b</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">(z)^(n) == a + I*b</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|- style="background: #dfe6e9;"
|- style="background: #dfe6e9;"
| [https://dlmf.nist.gov/1.11#Ex20 1.11#Ex20] || [[Item:Q420|<math>D_{1} = a_{1}</math>]]<br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>D_{1} = a_{1}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">D[1] = a[1]</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[D, 1] == Subscript[a, 1]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
| [https://dlmf.nist.gov/1.11#Ex20 1.11#Ex20] || <math qid="Q420">D_{1} = a_{1}</math><br><syntaxhighlight lang="tex" style="font-size: 75%; background: inherit;" inline>D_{1} = a_{1}</syntaxhighlight> || <math></math> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">D[1] = a[1]</pre></div> || <div class="mw-highlight mw-highlight-lang-mathematica mw-content-ltr" dir="ltr"><pre style="background: inherit;">Subscript[D, 1] == Subscript[a, 1]</pre></div> || Skipped - no semantic math || Skipped - no semantic math || - || -
|}
|}
</div>
</div>

Latest revision as of 11:00, 28 June 2021


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
1.11.E3 b k = α b k + 1 + a k subscript 𝑏 𝑘 𝛼 subscript 𝑏 𝑘 1 subscript 𝑎 𝑘 {\displaystyle{\displaystyle b_{k}=\alpha b_{k+1}+a_{k}}}
b_{k} = \alpha b_{k+1}+a_{k}
k = n - 1 𝑘 𝑛 1 {\displaystyle{\displaystyle k=n-1}}
b[k] = alpha*b[k + 1]+ a[k]
Subscript[b, k] == \[Alpha]*Subscript[b, k + 1]+ Subscript[a, k]
Skipped - no semantic math Skipped - no semantic math - -
1.11.E5 c k = α c k + 1 + b k subscript 𝑐 𝑘 𝛼 subscript 𝑐 𝑘 1 subscript 𝑏 𝑘 {\displaystyle{\displaystyle c_{k}=\alpha c_{k+1}+b_{k}}}
c_{k} = \alpha c_{k+1}+b_{k}
k = n - 1 𝑘 𝑛 1 {\displaystyle{\displaystyle k=n-1}}
c[k] = alpha*c[k + 1]+ b[k]
Subscript[c, k] == \[Alpha]*Subscript[c, k + 1]+ Subscript[b, k]
Skipped - no semantic math Skipped - no semantic math - -
1.11#E10Xa 1 j < k n z j z k = a n - 2 / a n subscript 1 𝑗 𝑘 𝑛 subscript 𝑧 𝑗 subscript 𝑧 𝑘 subscript 𝑎 𝑛 2 subscript 𝑎 𝑛 {\displaystyle{\displaystyle\displaystyle\sum_{1\leq j<k\leq n}z_{j}z_{k}=a_{n% -2}/a_{n}}}
\displaystyle\sum_{1\leq j<k\leq n}z_{j}z_{k} = a_{n-2}/a_{n}

sum(sum(z[j]*z[k], k = j + 1..n), j = 1..k - 1) = a[n - 2]/a[n]
Sum[Sum[Subscript[z, j]*Subscript[z, k], {k, j + 1, n}, GenerateConditions->None], {j, 1, k - 1}, GenerateConditions->None] == Subscript[a, n - 2]/Subscript[a, n]
Skipped - no semantic math Skipped - no semantic math - -
1.11#Ex4 D = b 2 - 4 a c 𝐷 superscript 𝑏 2 4 𝑎 𝑐 {\displaystyle{\displaystyle D=b^{2}-4ac}}
D = b^{2}-4ac

(- 4*(p)^(3)- 27*(q)^(2)) = (b)^(2)- 4*a*c
(- 4*(p)^(3)- 27*(q)^(2)) == (b)^(2)- 4*a*c
Skipped - no semantic math Skipped - no semantic math - -
1.11#Ex10 ρ = - 1 2 + 1 2 - 3 𝜌 1 2 1 2 3 {\displaystyle{\displaystyle\rho=-\tfrac{1}{2}+\tfrac{1}{2}\sqrt{-3}}}
\rho = -\tfrac{1}{2}+\tfrac{1}{2}\sqrt{-3}

rho = -(1)/(2)+(1)/(2)*sqrt(- 3)
\[Rho] == -Divide[1,2]+Divide[1,2]*Sqrt[- 3]
Skipped - no semantic math Skipped - no semantic math - -
1.11#Ex11 ρ 2 = e - 2 π i / 3 superscript 𝜌 2 superscript 𝑒 2 𝜋 𝑖 3 {\displaystyle{\displaystyle\rho^{2}=e^{-2\pi i/3}}}
\rho^{2} = e^{-2\pi i/3}

(rho)^(2) = exp(- 2*Pi*I/3)
\[Rho]^(2) == Exp[- 2*Pi*I/3]
Skipped - no semantic math Skipped - no semantic math - -
1.11#Ex13 p = ( - 3 a 2 + 8 b ) / 8 𝑝 3 superscript 𝑎 2 8 𝑏 8 {\displaystyle{\displaystyle p=(-3a^{2}+8b)/8}}
p = (-3a^{2}+8b)/8

p = (- 3*(a)^(2)+ 8*b)/8
p == (- 3*(a)^(2)+ 8*b)/8
Skipped - no semantic math Skipped - no semantic math - -
1.11#Ex14 q = ( a 3 - 4 a b + 8 c ) / 8 𝑞 superscript 𝑎 3 4 𝑎 𝑏 8 𝑐 8 {\displaystyle{\displaystyle q=(a^{3}-4ab+8c)/8}}
q = (a^{3}-4ab+8c)/8

q = ((a)^(3)- 4*a*b + 8*c)/8
q == ((a)^(3)- 4*a*b + 8*c)/8
Skipped - no semantic math Skipped - no semantic math - -
1.11#Ex15 r = ( - 3 a 4 + 16 a 2 b - 64 a c + 256 d ) / 256 𝑟 3 superscript 𝑎 4 16 superscript 𝑎 2 𝑏 64 𝑎 𝑐 256 𝑑 256 {\displaystyle{\displaystyle r=(-3a^{4}+16a^{2}b-64ac+256d)/256}}
r = (-3a^{4}+16a^{2}b-64ac+256d)/256

r = (- 3*(a)^(4)+ 16*(a)^(2)* b - 64*a*c + 256*d)/256
r == (- 3*(a)^(4)+ 16*(a)^(2)* b - 64*a*c + 256*d)/256
Skipped - no semantic math Skipped - no semantic math - -
1.11.E18 z 3 - 2 p z 2 + ( p 2 - 4 r ) z + q 2 = 0 superscript 𝑧 3 2 𝑝 superscript 𝑧 2 superscript 𝑝 2 4 𝑟 𝑧 superscript 𝑞 2 0 {\displaystyle{\displaystyle z^{3}-2pz^{2}+(p^{2}-4r)z+q^{2}=0}}
z^{3}-2pz^{2}+(p^{2}-4r)z+q^{2} = 0

(z)^(3)- 2*p*(z)^(2)+((p)^(2)- 4*r)*z + (q)^(2) = 0
(z)^(3)- 2*p*(z)^(2)+((p)^(2)- 4*r)*z + (q)^(2) == 0
Skipped - no semantic math Skipped - no semantic math - -
1.11.E20 - θ 1 - θ 2 - θ 3 = - q subscript 𝜃 1 subscript 𝜃 2 subscript 𝜃 3 𝑞 {\displaystyle{\displaystyle\sqrt{-\theta_{1}}\;\sqrt{-\theta_{2}}\;\sqrt{-% \theta_{3}}=-q}}
\sqrt{-\theta_{1}}\;\sqrt{-\theta_{2}}\;\sqrt{-\theta_{3}} = -q

sqrt(- theta[1])*sqrt(- theta[2])*sqrt(- theta[3]) = - q
Sqrt[- Subscript[\[Theta], 1]]*Sqrt[- Subscript[\[Theta], 2]]*Sqrt[- Subscript[\[Theta], 3]] == - q
Skipped - no semantic math Skipped - no semantic math - -
1.11.E22 z n = a + i b superscript 𝑧 𝑛 𝑎 𝑖 𝑏 {\displaystyle{\displaystyle z^{n}=a+ib}}
z^{n} = a+ib

(z)^(n) = a + I*b
(z)^(n) == a + I*b
Skipped - no semantic math Skipped - no semantic math - -
1.11#Ex20 D 1 = a 1 subscript 𝐷 1 subscript 𝑎 1 {\displaystyle{\displaystyle D_{1}=a_{1}}}
D_{1} = a_{1}

D[1] = a[1]
Subscript[D, 1] == Subscript[a, 1]
Skipped - no semantic math Skipped - no semantic math - -